Causes of Exocrine Pancreatic Insufficiency Other Than Chronic Pancreatitis - Kunovský, Lumír; Dítě, Petr; Jabandžiev, Petr; Eid, Michal; Poredská, Karolina; Vaculová, Jitka; Sochorová, Dana; Janeček, Pavel; Tesaříková, Pavla; Blaho, Martin; Trna, Jan; Hlavsa, Jan; et al. (Journal of clinical medicine, 2021)
Exocrine pancreatic insufficiency (EPI), an important cause of maldigestion and malnutrition, results from primary pancreatic disease or is secondary to impaired exocrine pancreatic function. Although chronic pancreatitis is the most common cause of EPI, several additional causes exist. These include pancreatic tumors, pancreatic resection procedures, and cystic fibrosis. Other diseases and conditions, such as diabetes mellitus, celiac disease, inflammatory bowel disease, and advanced patient age, have also been shown to be associated with EPI, but the exact etiology of EPI has not been clearly elucidated in these cases. The causes of EPI can be divided into loss of pancreatic parenchyma, inhibition or inactivation of pancreatic secretion, and postcibal pancreatic asynchrony. Pancreatic enzyme replacement therapy (PERT) is indicated for the conditions described above presenting with clinically clear steatorrhea, weight loss, or symptoms related to maldigestion and malabsorption. This review summarizes the current literature concerning those etiologies of EPI less common than chronic pancreatitis, the pathophysiology of the mechanisms of EPI associated with each diagnosis, and treatment recommendations.
Keywords: inflammatory bowel disease; pancreatic enzyme replacement therapy; celiac disease; pancreatic cancer; microbiome; exocrine pancreatic insufficiency; surgery; cystic fibrosis; pancreatic resection; diabetes